Statistical view on the "Gold Bug" story by E.A. Poe - Marek, Jaroslav; Deligiannaki, Katherine; Gkosdi, Maria (Slovenská technická univezita v Bratislave, 2016)
In the story Gold Bug of E. A. Poe we can meet with problem of connecting measurement. Unknown coordinates of treasure can be calculated by Least squares method. In this article our attention has been given to describe confidence domain by using statistical methods. To modeling of uncertainty of coordinates, the model of indirect measurement will be used.
Statistický pohled na povídku "Zlatý Skarabeus" od E.A. Poea
Keywords: statistical analysis, model of measurement, estimates of unknown parameters, confidence domain, E. A. Poe Gold Bug; statistická analýza, model měření, odhad neznámých parametrů, konfidenční oblast, E. A. Poe Zlatý skarabeus